Association of Obesity to The Prevalence and Severity of Gastroesophageal Reflux Disease (GERD) : A Systematic Review - Ridho Prip Trijasa Siringoringo; Priparty Intan Sukma Siringoringo; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Introduction: Gastroesophageal Reflux Disease (GERD) and obesity are two escalating global health crises with a well-documented association. While the link is known, a comprehensive synthesis of how different measures of obesity impact both the prevalence and objective severity of GERD is needed. This systematic review aims to evaluate and synthesize the current evidence on the association between obesity and the prevalence and severity of GERD. Methods: Following PRISMA guidelines, a systematic search was conducted across PubMed, Springer, Semantic Scholar, Google Scholar, and Wiley Online Library. We included observational studies and meta-analyses from the last ten years that examined the relationship between obesity (measured by BMI, waist circumference, etc.) and GERD (diagnosed via validated questionnaires, endoscopy, or pH monitoring) in adult populations. Twenty studies met the eligibility criteria and were included in the final analysis. Results: All 20 included studies reported a positive association between increased body mass and GERD risk or severity. Meta-analyses reported significant odds ratios for GERD in obese individuals, ranging from 1.73 to 4.25. A clear dose-response relationship was evident, with risk increasing with BMI category. Notably, central and visceral obesity were identified as particularly strong predictors of severe erosive esophagitis, sometimes more so than general BMI. Physiologically, obesity was linked to increased esophageal acid exposure and more frequent reflux events rather than primary esophageal dysmotility. Conclusion: This review confirms an unequivocal and powerful association between obesity and GERD. Increased body mass, particularly central adiposity, is a causal risk factor that drives both the prevalence and physiological severity of the disease. These findings underscore the urgent need to integrate weight management as a cornerstone of GERD clinical care and to address the obesity epidemic as a critical public health strategy to mitigate the growing global burden of reflux disease.